Programmatic diagnostic accuracy and clinical utility of Xpert MTB/XDR in patients with Rifampicin-resistant tuberculosis in Georgia - Pfurtscheller, Theresa; Tsutsunava, Ana; Maghradze, Nino; Gujabidze, Mariam; Bablishvili, Nino; Yerlikaya, Seda; Denkinger, Claudia M.; Tukvadze, Nestani; Gupta-Wright, Ankur (Open Forum Infectious Diseases, 2025)
Xpert MTB/XDR (Cepheid) is recommended by the World Health Organization for drug susceptibility testing in patients with tuberculosis, with potential for rapid detection of isoniazid and fluoroquinolone resistance. However, diagnostic accuracy and clinical utility in a programmatic setting are unknown.We evaluated the accuracy and clinical utility of Xpert MTB/XDR in patients with rifampicin-resistant pulmonary tuberculosis during programmatic implementation in Georgia between July 2022 and August 2024, using phenotypic drug susceptibility testing (DST) as a reference standard.An overall 140 patients were tested with Xpert MTB/XDR and phenotypic DST, and 94.9% and 33.8% had isoniazid and fluoroquinolone resistance by phenotypic DST, respectively. Xpert MTB/XDR showed 99.2% sensitivity (95% CI, 95.5%-100%) and 100% specificity (95% CI, 54.1%-100%) for isoniazid resistance. Sensitivity and specificity for fluoroquinolone resistance were 88.4% (95% CI, 74.9%-96.1%) and 100% (95% CI, 95.6%-100%). When indeterminate/invalid Xpert MTB/XDR results were included, 17.4% (8/46) and 6.2% (8/129) of patients with phenotypic fluoroquinolone and isoniazid resistance were missed. Median turnaround time for Xpert MTB/XDR was 1 day (IQR, 1-3) and median time to treatment was 4 days (IQR, 1-7). Phenotypic DST results took a median 43 days (IQR, 29-63) longer than Xpert MTB/XDR results. Finally, 95% (115/121; 95% CI, 89.5%-98.2%) of patients had fluoroquinolones appropriately prescribed based on Xpert MTB/XDR results.Programmatic data confirm the high accuracy of Xpert MTB/XDR, despite being below the World Health Organization target product profile targets for fluoroquinolones, with significantly faster time to results than phenotypic DST.
Gesehen am 27.08.2025